Retrospective Evaluation of Pulmonary Perfusion Scintigraphy for suspected Pulmonary Thromboembolism in Emergency Department - Kaplan, G. H.; Talay, N. B.; Koc, Z. P.; Oner, A. O.; Cete, Y.; Ozdemir, T.; Karayalcin, B. (Springer, 2009)
[Abstract Not Available]